A Christmas grace : a novel - Perry, Anne (Perry, Anne. Christmas novels., 2008)
With Christmas just around the corner, Thomas Pitt's sister-in-law, Emily Radley, is suddenly called from London to be with her dying aunt. Leaving her husband and two children behind, Emily makes the long journey to an all-but-forgotten town in the county of Connemara, on the western coast of Ireland. She soon discovers that a tragic legacy haunts the once close-knit community.